Power factor and THD improvement using PSIM software / Liyana Munirah Abas - Abas, Liyana Munirah (2013)
This project describes power factor correction using passive PFC and active PFC. Both techniques were simulated using power simulation software (PSIM). Passive filter was firstly tested but it did not give the proper result. Active PFC using buck converter was finally chosen and the result showed optimum power factor and minimum THD